PYTHON TEACHING METHODOLOGY: APPROACHES, CHALLENGES, AND BEST PRACTICES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The growing demand for programming skills has made Python an essential language in computer science education. This article explores various methodologies for teaching Python, focusing on effective pedagogical strategies, challenges faced by educators, and the best practices that can enhance learning outcomes. By analyzing different teaching models, including traditional classroom settings, online courses, and blended learning environments, this study aims to provide educators with a comprehensive guide to teaching Python effectively.